ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP IMPULSE BUYING MELALUI EMOTIONAL RESPONSE DI MATAHARI DEPARTMENT STORE TUNJUNGAN PLAZA SURABAYA - ANGGORO, SANDRA PUSPASARI (Universitas Katolik Widya Mandala Surabaya, 2012)
Changes in the form of renovations done by Matahari Departmen Store Tunjungan Plaza Surabaya, causing changes in the existing store atmosphere in the store. With the changes in store atmosphere, the response of consumers to the shopping environment (emotional responses) will also change and lead to impulse buying. The purpose of this study was to determine the positive effect of store atmosphere of emotional responses, knowing the positive influence of store atmosphere on impulse buying, investigate the effect of positive emotional responses to impulse buying, and know the emotional responses mediate the relationship of store atmosphere on impulse buying. The study design is a causal study involving one exogenous variables and two endogenous variables. This research data is the data interval with primary data through questionnaires that use 5 likert scale. Data analysis techniques using the structural equation model. The study findings suggest that the store atmosphere has a positive effect on emotional responses, Store atmosphere positive influence on impulse buying, Emotional responses positive influence on impulse buying, and Emotional responses mediate the relationship of store atmosphere on impulse buying.